Implementation of Proactive Recruitment Program for Indonesia National Police (POLRI) Candidates at Regional Police of the Riau Islands - Daniel Ganjar Kristanto; Pantius Drahen Soeling (UIN Sunan Gunung Djati, 2022)
Employee recruitment is an important function for the survival of the organization. The National Police provides opportunities for each Regional Police (Polda) to look for prospective Polri personnel who are in accordance with the needs in their area through a proactive recruitment program. This study aims to analyze the proactive recruitment program's effectiveness in meeting Polri personnel's needs in the area of Polda Kep. Riau. The qualitative research method is used with the post-positivism approach. The data obtained through observation, documentation and interviews were analyzed descriptively. The results showed that the implementation of proactive recruitment of the selection of Polri officers, Polda Kep. Riau in 2021 still encounters several obstacles; the lack of socialization and registration time for participants who come from outside the city, the assessment system is not yet valid and transparent and the minimum number of native children from the Kep area. Nevertheless, Riau was accepted and passed the selection. These constraints have implications for the declining reputation of the proactive recruitment system, potentially affecting public interest in participating in proactive recruitment programs in the future.